Access to the highest administrative courts - Piątek, Wojciech (Central European Public Administration Review, 2020)
Hearing a dispute by a court in a reasonable time is one of the crucial conditions for the existence of an effective judicial system as imposed by the European law and national legal orders. That requirement is contrary to the expectations of individuals to question the judgments of lower courts before the courts of the highest instance. The purpose of this article is to explore the question of values that should be taken into consideration by legislatures in a process of determining the access of administrative cases to the highest courts. The analysis is based on the example of Austrian and Polish legal systems. In both countries, there is a separate two-instance administrative judiciary. However, the conditions of the access to the Supreme Administrative Courts differ. In Poland, that access is unlimited, considering the constitutional principle of two-instance court proceedings. In Austria, the right in question is limited to cases deemed significant for broader interest, i.e. not only the one of the parties to the proceeding. An analysis of the normative consequences of each solution leads to the conclusion that procedural limitations concerning the access to the highest courts foster their role in preserving the uniformity of the case law and ensuring a high standard of its interpretation. A system with no limitations does not guarantee the determination of a concrete dispute in a reasonable time and thus cannot be considered effective.
Keywords: access to justice; administrative courts; Austria; effective appeal and judicial protection; ourt-administrative procedure; Poland